2017
DOI: 10.3389/fcell.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

PBX1 as Pioneer Factor: A Case Still Open

Abstract: Pioneer factors are proteins that can recognize their target sites in barely accessible chromatin and initiate a cascade of events that allows for later transcriptional activation of the respective genes. Pioneer factors are therefore particularly well-suited to initiate cell fate changes. To date, only a small number of pioneer factors have been identified and studied in depth, such as FOXD3/FOXA1, OCT4, or SOX2. Interestingly, several recent studies reported that the PBC transcription factor PBX1 can access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…This would indicate that, in this context, TALEs access promoters during early embryogenesis, facilitating chromatin accessibility of transcriptionally inactive genes, but Hox proteins are subsequently required to initiate transcription (Choe et al 2014). Accordingly, it was proposed that during early development, PBX proteins can mark genes for transcriptional activation as part of multimeric complexes, suggesting their potential roles as "pioneer factors" (for review, see Grebbin and Schulte 2017). However, a currently held definition of pioneer factors specifies that their binding to a DNA element is not dependent on pre-existing histone modifications that are indicative of gene activation (for reviews, see Iwafuchi-Doi and Zaret 2014;Donaghey et al 2018).…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
“…This would indicate that, in this context, TALEs access promoters during early embryogenesis, facilitating chromatin accessibility of transcriptionally inactive genes, but Hox proteins are subsequently required to initiate transcription (Choe et al 2014). Accordingly, it was proposed that during early development, PBX proteins can mark genes for transcriptional activation as part of multimeric complexes, suggesting their potential roles as "pioneer factors" (for review, see Grebbin and Schulte 2017). However, a currently held definition of pioneer factors specifies that their binding to a DNA element is not dependent on pre-existing histone modifications that are indicative of gene activation (for reviews, see Iwafuchi-Doi and Zaret 2014;Donaghey et al 2018).…”
Section: Partnerships Of Pbc Tfsmentioning
confidence: 99%
“…Recently, it has also been noted that PBX1 may act as a pioneer transcription factor, which is a type of transcription factor that can recognize and bind to their target sites even when chromatin is tightly wound rather than loose and easily accessible (Donaghey et al, 2018; Grebbin & Schulte, 2017). Few pioneer factors have been identified and thoroughly studied, but evidence from in vivo and in vitro studies suggests that PBX1 might belong to this category.…”
Section: Genetic Networkmentioning
confidence: 99%
“…Few pioneer factors have been identified and thoroughly studied, but evidence from in vivo and in vitro studies suggests that PBX1 might belong to this category. The three hallmarks of pioneer factor function reside in: (a) binding to target sites in closed chromatin, (b) increasing DNA access for other proteins, and (c) being actively involved in cell fate specification or cellular (re)programming (Grebbin & Schulte, 2017; Iwafuchi-Doi & Zaret, 2016). With respect to (a), it has been shown that PBX1 binds to target sites in promoter/enhancer regions of genes such as Dcx and Th before they become transcriptionally active, suggesting that PBX1 target sites for these genes could be located in closed chromatin at the time of binding (Brill et al, 2008; Grebbin & Schulte, 2017).…”
Section: Genetic Networkmentioning
confidence: 99%
“…Studies in zebrafish and mouse embryos, as well as in mammalian cell culture models, have shown that Pbx proteins bind with Myod1 on the promoters of a subset of Myod1 target genes, including Myog and mylpfa (Berkes et al, 2004;Cho et al, 2015;de la Serna et al, 2005;Dell'Orso et al, 2016;Heidt et al, 2007;Maves et al, 2007;Pliner et al, 2018). Pbx proteins can bind silent Myod1 target gene promoters prior to Myod1 binding and muscle differentiation, suggesting the potential for Pbx proteins to function as pioneer factors in skeletal muscle differentiation (Berkes et al, 2004;Cho et al, 2015;de la Serna et al, 2005;Dell'Orso et al, 2016; for discussion of Pbx proteins as pioneer factors, see Schulte, 2017 andSelleri et al, 2019). Pbx genes are broadly expressed during embryogenesis and are required for many aspects of mouse embryo development (reviewed in Moens and Selleri, 2006;and Selleri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%